Hubungan Fungsi Kognitif Dengan Keseimbangan Pada Lansia Di Jakarta - Ireina Karyn; Maria Dara Novi Handayani; Octavianus Darmawan (Bahasa Indonesia, 2021)
Introduction: The world is entering an aging population. With aging comes many challenges due to changes of the brain structure that affect both cognitive function and balance. The amount of cognitive function and balance impairment cases in the elderly are rising. If left unattended, it can cause numerous adverse effects in the elderly, eventually leading to the loss of the ability to perform activities of daily living. Studies have observed the relationship between cognitive impairment and balance in Indonesia, but only a few were conducted in Jakarta, specifically among elders in the nursing home. This study is aimed to observe the association between cognitive function and balance in the elderly.Methods: This is a secondary analysis using a previous study conducted in PSTW Budi Mulia Jakarta in 2016. Demographic data, cognitive function, and balance were assessed using the demographic questionnaire, Mini-Mental State Examination (MMSE), and Berg Balance Scale (BBS). Statistical analysis is conducted using IBM SPSS Ver 22.Results: Most respondents were female, aged 60-69 years old, had low education level, good MMSE score (53,3%), and a normal BBS (90,7%) score. We found a significant relationship between cognitive functions and balance (p=0,045).Conclusion: Cognitive function is related to balance impairment in the elderly. Key Words: balance, cognitive function, elderly